Pengembangan Game Simulasi Proses Pengisian Kartu Rencana Studi - Jarvis, Dominikus; Bata, Julius (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2023)
Completing the study plan card (KRS) is one of the most important processes in lectures. The problem that is often faced by first year students when doing KRS is that students do not know the steps for doing KRS. This paper proposes a simulation game as a solution to solve this problem. The focus of this paper is to explain the development process and the results that have been achieved. Game development is done using the ADDIE model. Game evaluation is done by using black box testing. Based on the black box test results, all game functionality can run. Therefore the game can be used for user testing